Sulfate assisted synthesis of α-type nickel hydroxide nanowires with 3D reticulation for energy storage in hybrid supercapacitors. (30th November 2021) - Li, Wei; Huang, Zhongzheng; Jia, Yaduo; Cui, Yunlong; Shi, Peng; Li, Tingting; Yue, Hongwei; Wang, Jinxiao; He, Weiwei; Lou, Xiaojie
Abstract : α-Type NSOH NWs with 3D reticulation were synthesized by a sulfate assisted hydrothermal reaction and exhibited a high capacity of 246.3 mA h g −1 at 1 A g −1 . The energy density of the NSOH NWs//AC HSCs is up to 59.8 W h kg −1 at 830.3 W kg −1 . Abstract : Nickel hydroxide, as a high high-efficiency electroactive material, is a promising electroactive material for advanced hybrid supercapacitors due to its high theoretical capacity, low-cost, and good thermal and chemical stabilities. Although various nanostructures of nickel hydroxide have been widely reported for energy storage devices, such as nanoparticles, nanosheets, nanoflowers, and so on, nickel hydroxide with one-dimensional nanowire morphology has been rarely investigated until now. Meanwhile, previous reports have shown that the energy storage performance of α-Ni(OH)2 is superior to other types of nickel hydroxides. Based on the above points of view, α type Ni(OH)2 nanowires with three-dimensional (3D) reticulation containing SO4 2− (abbreviated as NSOH NWs) were successfully obtained by a sulfate assisted hydrothermal approach in the present work and further employed as an electroactive material in hybrid supercapacitors (HSCs). The formation mechanism of the NSOH and the effects of SO4 2− are also discussed. Thanks to its novel 3D porous morphology and α-type phase structure, the as-prepared NSOH NW electrode presents a high specific capacity of 246.3 mA h g −1 at 1 A g −1, along with a good cycling stability of 91.7% after 4000 cycles. Meanwhile, the as-assembled NSOH NWs//AC HSCs can provide a high energy density of 59.8 W h kg −1 at a power density of 830.3 W kg −1 . The HSCs also show 91.5% specific capacity retention after 10 000 cycles. All above results manifest that the proposed NSOH NWs with 3D reticulation have significant potential for advanced HSC applications.